2017
DOI: 10.1016/j.eneco.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying away the risk of war and cross-border political crisis

Abstract: This paper investigates the behavior of crude oil prices, government bonds and stock market indices around outbreaks of severe international crises and wars. Using a constant-mean-return event study, we show that these events are associated with positive and significant abnormal returns on oil and bonds, which means that these two asset classes can potentially shelter shareholders from plummeting equity values during international crises. A formal safe haven analysis confirms this insight. Such price movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 91 publications
2
38
1
Order By: Relevance
“…Thereby, the WTI oil price reflects the global supply-and-demand situations. The fact that market prices are sensitive to political and military actions may have important implications for international investors seeking to diversify their portfolios effectively (Omar et al, 2016). Before 1986, the crude oil prices were strongly established by imposed price and production targets mainly by OPEC.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…Thereby, the WTI oil price reflects the global supply-and-demand situations. The fact that market prices are sensitive to political and military actions may have important implications for international investors seeking to diversify their portfolios effectively (Omar et al, 2016). Before 1986, the crude oil prices were strongly established by imposed price and production targets mainly by OPEC.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…Energy and equity markets can be shaken by profound geopolitical changes and the friction and tension that they invariably generate, as well as by major security risk generating episodes. So can their association (Wacziarg, 2012;Omar et al 2016;Kollias et al 2013a). This is particularly true for the oil markets given the strategic nature of this commodity and the fact that a large share of the global oil supply is produced in the Middle East.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the characteristics and the dynamics of the domestic as well as the international political environment significantly affect the economy, markets and market agents' sentiment and behavior (inter alia: Wolfers and Zitzewitz, 2009;Bialkowski et al 2008;Fielding, 2003;Gaibulloev and Sandler, 2008). Fluctuations in the political scene or one-off events can exert a noteworthy effect in equity markets; in the cross correlation of assets; in portfolio allocation and diversification decisions (inter alia: Omar et al 2016;Asteriou and Siriopoulos, 2003). Events such as elections, governmental changes, political upheavals, civil strife or more violent episodes such as terrorist attacks, affect economic performance and asset markets (inter alia: Guidolin and La Ferrara, 2010;Drakos and Kallandranis, 2015;Gaibulloev and Sandler, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gaibulloev and Sandler in 2008 show that the international political environment influences the agents' sentiment and behaviour, the economy and markets. Additionally, Kollias et al (2013) as well as Omar et al (2016) have demonstrated that instabilities of political climate may increase risks in equity markets, in addition to portfolio allocation and diversification. Furthermore, Choudhry (2010) and Drakos and Kallandranis (2015) argued that many events such as elections, political upheavals, terrorist attacks, simply geopolitical friction, armed conflicts and others distress economic performance increase the uncertainty in global markets.…”
Section: Introductionmentioning
confidence: 99%